A Study on Women’s Rights under Labor Laws in India: Ensuring Gender Equality and Women's Protection in Indian Labor Laws (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The main aim of this article is to deliver the rights under labor laws which are over to the women’s based on the Indian constitution and conventions. Ensuring gender equality, and protection of women’s interests in labour law is a key ingredient to improving social justice. This article will discuss the various standards conventions as well as domestic law for the promotion and protection of women’s interests in labour law, focusing specifically in the issues of equal employment opportunities, wage disparity, sexual harassment at the workplace, and maternity benefit.